Exploring the twin tracks of economic and IIPA governance reforms in the two states of Madhya Pradesh and Andhra Pradesh - Radhika Kumar (2017)
Second-generation economic reforms in India, a feature of the mid-1990s, have also included subnational level reforms and restructuring. These reforms have also run the course of about 15 years with there being many temporal and spatial variations with regard to experiences of individual states. However, common to this reform experience are three features. First, that funding for these reforms has largely come from international financial institutions (IFIs), in particular, the World Bank and the Asian Development Bank (ADB). Second, and drawing from the first, is the feature that the framework for reforms, development sectors covered as well as pace, prospects and outcome of reforms are determined by the same lending agencies. Third, reforms so initiated have invariably incorporated 'good governance' strategies. What is paradoxical then is that reform programmes which have been tailor-made to suit the economic specificities of a given state actually prescribe similar remedies for all. Increased economic autonomy of state governments in the post-liberalisation period has been limited to courting the IFIs for reform-linked loans. These loans come with concomitant conditionalities albeit made politically palatable by the terminology of good governance. The neoliberal model of development has found a pan-India appeal with there being little or no state-level variations in its adoption and implementation. - Reproduced.
Keywords: International monetary systems; Public administration; Good governance; Economic reform